Larval Strategy of Two Species of Seed-Feeding Chalcidoidea Parallels that of Parasitoid Koinobionts - Jansen González, Sergio (2020)
The association between ontogenetic processes in plants and phytophagous insects is not traditionally considered in studies of insect-plant interactions. Angiosperm seeds impose important constraints on seed predators; the structural complexity of seeds and the progressive accumulation of resources throughout their development limit the time windows when resources can be retrieved by the predator. Some holometabolous insects deposit their eggs inside immature seeds, with the immature stages of both insect and plant cohabiting in a space with limited but potential resources. We studied the larval development of Megastigmus transvaalensis (Hussey, 1956) (Chalcidoidea: Megastigmidae) and Bephratelloides pomorum (F., 1804) (Chalcidoidea: Eurytomidae) and the seed development of their respective hosts, Schinus terebinthifolia (Raddi, 1820) (Anacardiaceae) and Annona crassiflora (Mart., 1841) (Annonaceae). Our results show that both M. transvaalensis and B. pomorum oviposit in immature fruits, whose protective tissues surrounding the seeds are softer. The first larval instar interferes little with the development of the seed, allowing both seed and plant embryo to continue growing. When the infested seed reaches the size of a mature, non-infested seed, the larva grows rapidly and consumes most of it. M. transvaalensis induces minor modifications in the endosperm cells, while B. pomorum does not induce any visual modifications. The strategy of allowing seed/plant embryo to continue growing shows similarities to the endoparasitic koinobiont strategy followed by some chalcid parasitoids, which keep their host alive while feeding upon it. Future studies should be expanded to other chalcid seed predators in order to understand the evolution of convergent patterns among seed-feeding insects and its evolution in relation to parasitoid strategies inside the group.